The Quality of Recovery after Dexamethasone, Ondansetron, or Placebo Administration in Patients Undergoing Lower Limbs Orthopedic Surgery under Spinal Anesthesia Using Intrathecal Morphine. A Randomized Controlled Trial - Eduardo Toshiyuki Moro; Miguel Antônio Teixeira Ferreira; Renyer dos Santos Gonçalves; Roberta Costa Vargas; Samira Joverno Calil; Maria Alice Soranz; Joshua Bloomstone (Anesthesiology Research and Practice)
Intrathecal morphine is widely and successfully used to prevent postoperative pain after orthopedic surgery, but it is frequently associated with side effects. The aim of this study was to evaluate the effect of dexamethasone or ondansetron when compared to placebo to reduce the occurrence of these undesirable effects and, consequently, to improve the quality of recovery based on patient’s perspective. Methods. One hundred and thirty-five patients undergoing lower extremity orthopedic surgery under spinal anesthesia using bupivacaine and morphine were randomly assigned to receive IV dexamethasone, ondansetron, or saline. On the morning following surgery, a quality of recovery questionnaire (QoR-40) was completed. Results. No differences were detected in the global and dimensional QoR-40 scores following surgery; however, following postanesthesia care unit (PACU) discharge, pain scores were higher in patients receiving ondansetron compared with patients who received dexamethasone. Conclusion. Neither ondansetron nor dexamethasone improves the quality of recovery after lower limbs orthopedic surgery under spinal anesthesia using intrathecal morphine.